19 Diagnostic benefits of clinical CMR. (May 2018) - Dancy, Luke; Bromage, Daniel; Sado, Daniel
Abstract : Introduction: In clinical practice, CMR is most often used to make or confirm a diagnosis with the aim of improving management. In the EuroCMR registry in 62% of cases management is changed by CMR and in 9% the CMR diagnosis is different to that made before. We believe that a key role of CMR is the finding of a normal study where previous tests had resulted in the patient being labelled abnormal. This is not an outcome specifically addressed in the EuroCMR registry. Methods: 444 consecutive patient scans were reviewed from between July and December 2017. Diagnoses and management changes were recorded. Results: Of 444 patients, a new or unexpected diagnosis was found in 23%. In 62% of cases a change in management resulted. Importantly in 11% of cases the CMR was normal where previous imaging had suggested an abnormality. Most commonly this was underestimation of the left ventricular function. Conclusion: In line with the EuroCMR registry, CMR has an impact on patient management in just under two thirds of cases. However, there was a high proportion (11%) of patients for whom the CMR was normal despite previous imaging suggesting abnormality; most frequently this was a finding of normal LV function where other tests had suggested it would be low. This is important to consider for future research into patients with mid-range ejection fraction and clinically it prevents patients from potentially being labelled and treated for a problem that they may not have.